2004
DOI: 10.1016/j.joca.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Synovial lining macrophages mediate osteophyte formation during experimental osteoarthritis

Abstract: These results indicate the synovial macrophage to be a pivotal cell in the synovium mediating osteophyte formation and other OA-related pathology, like fibrosis, during experimental OA. Production of growth factors and induction of synovial activation by these cells may play a crucial role in this event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
284
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(298 citation statements)
references
References 32 publications
(32 reference statements)
10
284
3
1
Order By: Relevance
“…We have previously reported the presence of mature tissue macrophages closely associated with bone (6). It is also known that macrophages can express and secrete osteoactive cytokines (35), matrix metalloproteinases (36), and bone morphogenetic proteins (35).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have previously reported the presence of mature tissue macrophages closely associated with bone (6). It is also known that macrophages can express and secrete osteoactive cytokines (35), matrix metalloproteinases (36), and bone morphogenetic proteins (35).…”
Section: Discussionmentioning
confidence: 90%
“…The intimate relationship between these two systems has been primarily demonstrated in pathological conditions. Macrophages were recognized during fracture repair (33), arteriole calcification (34), and at sites of osteophyte formation in OA animal models (35). Additionally, macrophages were found at sites of pathological bone destruction (36) and contributed to systemic mechanisms in an animal model of osteoporosis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, macrophages can produce large quantities of growth factors, enzymes, and proinflammatory cytokines. It has previously been shown that macrophages enhance osteophyte growth in animal models of OA (1,2). Furthermore, it is possible that macrophages play a role in the maintenance and progression of the disease by their contribution to synovial fibrosis, cartilage catabolism, and maintenance of an inflammatory state in the joint (3,4) by production of growth factors (5,6), enzymes (7), and cytokines, respectively (8,9).…”
mentioning
confidence: 99%
“…Changing weight mechanics and pressure forces as well as alterations in oxygen tension and dynamic fluid pres-sure appear to be influential factors in osteophyte formation [14]. Mesenchymal stem cells of the synovium or periostium are likely precursors, with synovial macrophages and a milieu of growth factors and extracellular matrix molecules acting as probable mediators in this process [29].…”
Section: Phase IIImentioning
confidence: 99%